Stanley Fish, America's Enfant Terrible : The Authorized Biography - Olson, Gary A., 1954- (Book collections on Project MUSE., 2016)
"A chronological narrative of the life and an intellectual chronicle and explication of the major works of legal scholar, literary critic, and public intellectual Stanley Fish, who is considered one of the century's most original and influential literary theorists"--